Is breast cancer a civilization disease? Common components of type 2 diabetes and breast cancer - Wijas, Karolina; Szala-Czerwonka, Karolina; Rejmer, Adrian; Woś, Natalia; Rojek, Katarzyna; Bednarz, Lucjan; Bialic, Kinga; Bakalarczyk, Rafał; Bialic, Artur; Majewski, Paweł (Journal of Education, Health and Sport, 2023)
Diabetes Mellitus is one of the most common civilization diseases.The incidence of this disease has been increasing over the last few decades. Research is still being conducted to show the relationship between diabetes and other diseases. Based on these studies, it can be concluded that it also plays a role in the development of cancer. In this review, we focus on analyzing studies on the relationship between type 2 diabetes and breast cancer. We show the influence of diabetes components on the pathomechanism of breast cancer development. We focus on hyperinsulinemia, inflammatory processes, oxidative stress, and obesity, which often accompany type 2 diabetes. Based on the analyzed studies, it can be concluded that type 2 diabetes is a significant factor contributing to cancerous processes associated with breast cancer. In this review, we used articles available in the PubMed database.